2020
DOI: 10.1111/1462-2920.14935
|View full text |Cite
|
Sign up to set email alerts
|

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress

Abstract: Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 118 publications
5
49
1
Order By: Relevance
“…We demonstrate that daily cycling and sampling time, especially light, influence the proportion of Symbiodiniaceae cells that are closely associated with bacteria. This is concordant with previous studies that showed Symbiodiniaceae bacterial communities change with temperature [41], and that bacterial density increases with culture age in the dinoflagellates Heterocapsa circularisquama, Alexandrium catenella, and Protoceratium reticulatum [11,80]. It was also shown in H. circularisquama that the density of intracellular bacteria increases when the dinoflagellate culture is switched to continuous darkness [80], an increase we also report here during the night period.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We demonstrate that daily cycling and sampling time, especially light, influence the proportion of Symbiodiniaceae cells that are closely associated with bacteria. This is concordant with previous studies that showed Symbiodiniaceae bacterial communities change with temperature [41], and that bacterial density increases with culture age in the dinoflagellates Heterocapsa circularisquama, Alexandrium catenella, and Protoceratium reticulatum [11,80]. It was also shown in H. circularisquama that the density of intracellular bacteria increases when the dinoflagellate culture is switched to continuous darkness [80], an increase we also report here during the night period.…”
Section: Discussionsupporting
confidence: 93%
“…Metabarcoding data indicated that bacterial communities associated with Symbiodiniaceae cultures were largely comprised of Hyphomicrobium, Methylobacterium, Sphingomonas, Marinobacter, Labrenzia, Balneola, Algiphilus, Rhodobacteraceae, Phycisphaeraeae, and Roseitalea. Marinobacter, Labrenzia, and Muricauda were previously found to be abundant in a wide range of Symbiodiniaceae cultures [39][40][41], indicating the conservation of specific bacterial associates across Symbiodiniaceae species, coral hosts, and coral host location. Marinobacter enhances the growth of Scrippsiella trochoidea, presumably by producing vibrioferrin, a siderophore that promotes iron uptake by the dinoflagellate [18].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…During coral bleaching (the breakdown of the symbiosis between corals and Symbiodiniaceae), coral microbiomes may shift from healthy communities towards opportunistic taxa such as Vibrio (Bourne et al., 2008). Furthermore, a recent in vitro experiment showed that warming caused changes in Symbiodiniaceae culture‐associated bacterial communities, and that compared to Cladocopium C1 and Breviolum sp., the heat‐tolerant Durusdinium trenchii had the most stable bacterial community under heat stress (Camp et al., 2020). Additionally, environmental adaptation of corals probably involves multiple members of the meta‐organism (e.g., coral, bacteria, Symbiodiniaceae; van Oppen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%